Preparation and application of starch nanocrystals for reinforcing in rice starch film - Piyada Kaewpool (Prince of Songkla University Faculty of Agro-Industry (Packaging Technology), 2013)
Thesis (M.Sc., Packing Technology)--Prince of Songkla University, 2010